Functional Relevance of Citrulline in the Vegetative Tissues of Watermelon During Abiotic Stresses - Song, Qiushuo; Joshi, Madhumita; DiPiazza, James; Joshi, Vijay (Frontiers in Plant Science, 2020)
A non-protein amino acid, citrulline, is a compatible solute involved in the maintenance of cellular osmolarity during abiotic stresses. Despite its significance, a coherent model indicating the role of citrulline during stress conditions has not yet emerged. We have used watermelon, naturally rich in citrulline, as a model to understand its accumulation during drought stress and nitrogen perturbation using transcriptomic and metabolomic analysis. Experiments were performed in the semi-controlled environment, and open field to study the accumulation of drought-induced citrulline in the vegetative tissues of watermelon by monitoring the stress treatments using physiological measurements. The amino acid profiling of leaves and stems in response to drought stress showed up to a 38 and 16-fold increase in citrulline content, respectively. Correlation between amino acids indicated a concomitant activation of a metabolic pathway that included citrulline, its precursor (ornithine), and catabolic product (arginine). Consistent with its accumulation, the gene expression analysis and RNA-Sequencing confirmed activation of citrulline biosynthesis-related genes - Ornithine carbamoyl-transferase (OTC), N-acetylornithine deacetylase (AOD) and Carbamoyl phosphate synthases (CPS), and down-regulation of catabolic genes; Arginosuccinate lyase (ASL) and Arginosuccinate synthases (ASS) in drought-stressed leaf tissues. Based on the relative abundance in the nitrogen-depleted vegetative tissues and down-regulation of genes involved in citrulline biosynthesis, we also demonstrated that the nitrogen status of the plant regulates citrulline. Taken together, these data provide further insights into the metabolic and molecular mechanisms underlying the amino acid metabolism under environmental stress and the significance of non-protein amino acid citrulline in plants.